AN ANALYTICAL METHOD OF ESTIMATING VALUE-AT-RISK ON THE BELGRADE STOCK EXCHANGE - D. Obadović, Milica; M. Obadović, Mirjana (Economic Annals, 2009)
This paper presents market risk evaluation for a portfolio consisting of shares that are continuously traded on the Belgrade Stock Exchange, by applying the Value-at-Risk model – the analytical method. It describes the manner of analytical method application and compares the results obtained by implementing this method at different confidence levels. Method verification was carried out on the basis of the failure rate that demonstrated the confidence level for which this method was acceptable in view of the given conditions.